Negative income tax and guaranteed income system as redistributive models - Carlos Bilbao Contreras (Opción, 2021)
The need for a new articulation of welfare benefits is motivated by the global economic crisis. This led to the increase in people and families in poverty in the industrialized world and in developing countries by reducing international trade. The situation described requires solutions aimed at the establishment of a care system in the administrations of the affected countries. The models for its articulation are limited on the one hand to the implementation of a Negative Income Tax and on the other to a Guaranteed Income System.